Environmental Protection Tax and Green Investment on Green Innovation: Digitalization, ESG, CSR as Mediation - Putri Az Zahra Nodhiva; Sofi Salfira Anjharsari; Farah Margaretha Leon (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to identify variables that influence environmental tax protection, digitalization, ESG, CSR and green investment variables on green innovation. The research conducted is quantitative and the data obtained is secondary data. Data were obtained from companies that publish their financial statements and annual reports. The unit of analysis used in this study is manufacturing companies listed on the Indonesia Stock Exchange. Managerial implications for company management with operational efficiency and long-term sustainability of the company. Companies can develop new products that are more environmentally friendly, more energy efficient production processes, or new technologies to recycle waste. Management can consider strengthening and expanding CSR practices including environmental commitments as an integral part of their business strategy. Stakeholders need to see transparency in communication about green investment and green innovation so that they can improve financial performance and company value.